2011
DOI: 10.1159/000323219
|View full text |Cite
|
Sign up to set email alerts
|

Abciximab Does Not Prevent Ischemic Lesions Related to Cerebral Angiography: A Randomized Placebo-Controlled Trial

Abstract: Background: To assess the efficiency of IIb/IIIa platelet receptor inhibition by abciximab in the prevention of silent embolism during digital subtraction angiography. Methods: In this randomized, double-blind, prospective study, pre- and postangiographic diffusion-weighted magnetic resonance imaging (DWI) of 184 participants was evaluated for the occurrence of silent embolism. Results: No significant relationship was found between the patients receiving abciximab before digital subtraction angiography (15 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
4
1
Order By: Relevance
“…Similar lesions were also observed with the injection of PBS at a rate of 0.16ml/min 13 . T2 abnormalities were similar to those observed in patients who undergo routine cerebral angiography 23, 24 .…”
Section: Safety Of Ia Injection After Strokesupporting
confidence: 78%
“…Similar lesions were also observed with the injection of PBS at a rate of 0.16ml/min 13 . T2 abnormalities were similar to those observed in patients who undergo routine cerebral angiography 23, 24 .…”
Section: Safety Of Ia Injection After Strokesupporting
confidence: 78%
“…Diffusion-weighted MRI (DWI) reveals a relatively high rate of ischemic events, most of which do not cause overt neurological deficits; therefore, it is well known that silent microembolism or cerebral ischemia are much more frequent than actual clinical events. DWI studies have indicated that 10–40% of patients have clinically silent embolism during such procedures [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…1 The plausible embolic sources of SECI, suggested from the previous studies, are thrombus formed from the catheter by platelet activation, dislodgement of the atheroma from the aortic arch by mechanical stress, 13 and air embolism. 15 Activation of the platelets by catheterization was revealed by previous studies using platelet flow cytometry, 16 and the platelet membrane activation markers were predictive for increased risk of ischemic events after catheterization. 17 In our study, the factors related to atherosclerotic burden (atherosclerosis score and the severity of coronary artery disease) or mechanical stress (number and size of the catheter used, total procedure time, and fluoroscopy time) did not differ by the occurrence of SECI.…”
Section: Discussionmentioning
confidence: 93%